Exploring the organisational drivers of workplace deviance: a systematic review of recent literature - Ruslan, Mohd Sufian; Abdul Wahat, Nor Wahiza; Ismail, Ismi Arif; Ismail, Suriani (Human Resources Management Academic Research Society (HRMARS), 2024)
This systematic literature review (SLR) explores the organisational drivers of workplace deviance, focussing on recent studies to identify key factors influencing deviant behaviours in organisational settings. Workplace deviance, encompassing both organisational and interpersonal misconduct, poses significant challenges to organisational effectiveness and employee well-being. Despite extensive research, understanding the organisational determinants of such behaviours remains fragmented. The problem is particularly pronounced in diverse sectors, where varying organisational cultures and leadership styles influence employee behaviour. This review synthesises findings from 32 peer-reviewed articles published between 2022 and 2024, using a systematic approach guided by the PRISMA Statement. The methodology involved an extensive search of scholarly articles from two reputable databases, which are Scopus and Web of Science, followed by rigorous screening and analysis of relevant studies. The finding was divided into three themes which is (1) Organisational Justice and Workplace Deviance, (2) Psychological and Social Dynamics of Workplace Deviance, and (3) Leadership and Organisational Behaviour on Workplace Deviance. Results indicate that organisational justice, workplace environment, and leadership styles are the primary drivers of deviant behaviour. The findings suggest that addressing organisational drivers through targeted interventions can reduce workplace deviance, ultimately enhancing organisational performance and employee satisfaction. This review improves the existing literature by delivering a thorough examination of the organisational elements influencing workplace deviance and presenting insights for future research and practical implementations.